(untitled) (Acta Entomologica Serbica, 2014)
In this study, the following six long-legged fly species (Diptera, Dolichopodidae) collected in the East Azerbaijan province during 2010-2013 are new records for the Iranian fauna: Chrysotimus molliculus (Fallén, 1823); Hercostomus apollo (Loew, 1869); Hydrophorus balticus (Meigen, 1824); Medetera meridionalis Negrobov, 1967; Orthoceratium lacustre (Scopoli, 1763) and Poecilobothrus principalis (Loew, 1861). General geographic distribution of the species and supplementary figures are provided.